Gene Mutations and Polymorphisms of TP53 and FHIT in Chronic Esophagitis and Esophageal Carcinoma - Fedossi Silveira, Aparecida Perpetuo [UNESP]; Manoel-Caetano, Fernanda da Silva [UNESP]; Aoki, Sergio [UNESP]; Tomonari Yamasaki, Lilian Hiromi [UNESP]; Rahal, Paula [UNESP]; Silva, Ana Elizabete [UNESP] (Int Inst Anticancer Research, 2011)
Aim: The aim of this study was to investigate genetic changes of the TP53 (tumor protein p53) and FHIT (fragile histidine triad) genes in precursor lesion such as chronic esophagitis (CE) and in esophageal squamous cell carcinoma (ESCC). Materials and Methods: PCR-Single Strand Conformation Polymorphism (SSCP) analysis and DNA sequencing in 30 CE and 10 ESCC specimens were performed. Results: DNA sequencing indicated two novel mutations in the TP53 exons 5 (codon 147) and 6 (codon 197) in 219 SSCP positive cases of ESCC, but no mutation was found in the CE. The SIFT (Sorting Intolerant From Tolerant) web-based program showed that missense variant at codon 197 of TP53 could affect the protein function. Additionally, polymorphisms of the TP53 exon 4 (codon 36 and 72) and of the FHIT exon 7 (codon 88) were observed in 4/11(36%) cases of CE and 619 (67%) SSCP positive cases of ESCC after DNA sequencing. Conclusion: TP53 gene mutations are not common events in CE, but are frequent in ESCC, and as polymorphisms of TP53 and FHIT may confer a greater risk for the development of esophageal carcinoma, further studies are required.
Keywords: Mutations; Polymorphism; TP53; FHIT; Chronic esophagitis; esophageal carcinoma